L’économique de l’habitation : une revue de lalittérature - D’Amours, Alban; Nadeau, Léandre (L'Actualité économique, 1974)
AbstractThis article has a two-fold purpose: first, to offer as complete an inventory aspossible of the literature written on the economics of housing, classifying thisliterature according to subject matter (in this sense, the article takes on theappearance of an annotated bibliography); and second, to take a hard look at thepresent state of economic theory in this field. The article is divided into the following six sections: 1) existing surveys;2) studies related to long-term cycles in residential construction; 3) theoriesexplaining short-term fluctuations; 4) verbal models; 5) econometric models;6) other studies. Some emphasis has been given to the authors' two principal conclusions. In theiropinion, the "residual" vision and the countercyclical hypothesis have not beenadequately tested in the past. Furthermore, the authors bring to light evidence,both theoretical and factual, which contradicts this theory (see Section 3). Then,in Section 5, the authors attempt to show how econometric models, except in the mostrecent papers, fail to take into account, adequately, the relationships between thehousing and mortgage markets and the builders. In addition, it is contended thatthese models are not truly representational of the whole sector, in that they areoften nothing more than simple demand or supply equations, or, even worse, neitherone nor the other.